Empathy Impairment in Individuals With Autism Spectrum Conditions From a Multidimensional Perspective: A Meta-Analysis - Song, Youming; Nie, Tingting; Shi, Wendian; Zhao, Xudong; Yang, Yongyong (Frontiers in Psychology, 2019)
Background: Although empathy has always been considered to be impaired in individuals with autism spectrum conditions (ASCs), the relevant findings have been inconsistent. The present meta-analysis aims to determine which empathy components are impaired and how culture, gender and age moderate such empathy impairment. Methods: By using “Autism”, “Asperger Syndrome”, “Empathy” and related Chinese synonyms as keywords, we searched the databases of Weipu, Wanfang, CNKI, Web of Science, Science Direct, SpringerLink and Elsevier through “subject” and “keyword” searches. We also conducted a manual search according to the references. In total, 51 studies from Eastern and Western countries were included in this meta-analysis, which comprised 144 independent effects, 2,095 individuals with ASCs and 2,869 controls without ASCs. For the retrieved data, Hedge’s g was taken as the quantitative measure of effect, and CMA V2.0 software was used for publication bias tests (by using Rosenthal’s Classic Failsafe-N and Egger’s methods), heterogeneity tests (by using a Q test, I2 test and H test) and a moderating effect test (by using a univariate regression model). Results: The results showed that the empathy impairment evident in individuals with ASCs is component specific; that is, trait-cognitive empathy, trait-empathic concern, state-cognitive empathy and state-empathic concern are impaired, whereas state-empathic accuracy remains intact, and trait-empathic accuracy is superior to the trait-empathic accuracy in neurotypical individuals. The univariate regression model showed that gender moderates the impairment of the trait-empathic concern, trait-empathic accuracy and state-cognitive empathy in autistic individuals and that age moderates the impairment of the trait-cognitive empathy, trait-empathic accuracy, state-empathic concern and state-empathic accuracy in autistic individuals. However, culture does not moderate any empathy components (trait-cognitive empathy, trait-empathic concern or state-cognitive empathy) involved in the present meta-analysis. Conclusions: These findings contribute to ending the controversy over the empathic integrity of individuals with ASCs and shed some light on future research about the empathy impairment of autistic individuals. More specifically, subsequent studies should distinguish specific empathy components and consider the role of gender and age when demonstrating empathy impairment in individuals with ASCs. Moreover, related studies based on Asian collectivist cultural samples and female samples should be further enriched.